An Evaluation of Emergency Remote Teaching in Engineering Based on a Community of Inquiry Framework - Smith, Jovanca; Singh, Arvind; Thurab-Nkhosi, Dianne; Maharaj, Sharad; Maharaj, Chris (Journal of Engineering Education Transformations, 2025)
One major effect of the Covid-19 pandemic was the abrupt shift from traditional face-to-face (f2f) teaching and learning to emergency remote teaching (ERT). Student evaluations and reflections by lecturers indicate that the move to the predominantly online environment during the Covid-19 pandemic posed both challenges and opportunities. To capitalize on the opportunities afforded by ERT that can be utilized in another similar event or in movement from f2f to virtual classrooms, it is important to interrogate the challenges and factors that facilitated the transition to online learning. This paper utilizes a community of inquiry framework (CoI) to investigate the components of teaching styles, assessment styles, and student demographics on engineering students' performance during ERT at a top traditional f2f university in the Caribbean. A survey conducted was informed by CoI and student environment during the ERT transition. A quantitative study with regression analysis of survey data was utilized. Qualitative responses were also captured and analysed. The study has found that a teaching presence which demonstrated clear course design, facilitation and communication was a significant contributing factor to a comfortable online learning transition. Online learning was also impacted by aspects of the home environment like family support, distractions, and quality of living that contributed to a difficult transition.